Research and Design on Personalized Mobile Search Agent - Zhenwei He; Ruochen Zou; Weibin Zhong; Liyun Yan (Dianxin kexue)
Mobile search has become one of the most important mobile internet applications. With the development of intelligent terminal technology and search engine technology，it’s possibility to improve the user’s search experience. The personalized search requirement of mobile users was analyzed，and a personalized mobile search agent model was proposed，in conjunction with the mobile intelligent terminal capacity and commercial search engine’s ability to meet users’ personalized search habits and diverse needs of mobile search service.